The politics of provocation : participation and protest in Israel - Wolfsfeld, Gadi (State University of New York Press, 1988)
Annotation A straightforward presentation in which theoretical/conceptual orientation is both novel and grounded in sound testing with extensive data. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Israel -- Politics and government.; Political participation -- Israel.; Radicalism -- Israel.; Participation politique -- Israël.; Radicalisme -- Israël.; Israël -- Politique et gouvernement.; POLITICAL SCIENCE -- Political Process -- General.; Political participation; Politics and government; Radicalism; Israel; Politische Beteiligung